Penerapan Pembelajaran Kooperatif Model STAD untuk Meningkatkan Kemampuan Siswa Menyelesaikan Soal Akar Pangkat Tiga Mata Pelajaran Matematika di Kelas VI SDN Getas 1 Semester 1 Tahun Pelajaran 2021/2022 - Susi Dyah Fatmawati (Action Research Journal, 2022)
The application of the STAD cooperative learning model to improve students' ability to solve cube root problems in mathematics in class VI SDN Getas 1 semester I for the 2021/2022 school year. The low formative test in mathematics lessons on the cube root material of 26 students who completed only 4 students (15%). The average value is 53. This is because students have not memorized multiplication and division. From this the author wants to improve students' ability to solve cube root problems by conducting research in the form of classroom action research by applying STAD cooperative learning model because this learning includes lectures, group work, discussion, giving quizzes or tests as drills for students. The results of the first cycle of learning the average value of 63 students, and in the second cycle has increased to 84. Of the 26 students who completed the first cycle 10 children (38%), in the second cycle to 22 children (84%). This proves that the STAD cooperative learning model can improve students' ability to solve cube root problems as evidenced by the increase in the average value of students in learning.